1984
DOI: 10.1063/1.95074
|View full text |Cite
|
Sign up to set email alerts
|

Modulation doping in GexSi1−x/Si strained layer heterostructures

Abstract: We report the first observation of the modulation doping effect in Si/Ge0.2Si0.8 heterojunctions grown by molecular beam epitaxy. Peak hole mobilities of ∼3300 cm2 V−1 s−1 have been observed at 4.2 K. These values, although nonoptimum, are comparable to the best reported values for holes in Si/SiO2 inversion layers. Low temperature, angular dependent, Shubnikov–de Haas measurements have demonstrated the two-dimensional nature of the hole gas and yield a surface carrier density of 3.5×1011 cm−2. From the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(48 citation statements)
references
References 14 publications
1
46
0
1
Order By: Relevance
“…For example, substrate-induced (global) or processinduced (local) uniaxial straining of Si, Ge-, and III-V (e.g., GaAs) alters the band structure so as to enhance the performance of metal-oxide-semiconductor field-effect-transistors (MOSFETs). [14][15][16][17][18][19][20][21][22] A few review articles have covered aspects such as uniaxial and biaxial strain on carrier mobility in MOSFETs, [23][24][25][26] with a theoretical analysis of the physics of strained MOSFETs for different wafer surface orientations, channel directions, gate electric fields, and materials. 23,24,26 These studies have positive implications for similar investigations in bendable or flexible electronics.…”
Section: Historical Perspectivementioning
confidence: 99%
“…For example, substrate-induced (global) or processinduced (local) uniaxial straining of Si, Ge-, and III-V (e.g., GaAs) alters the band structure so as to enhance the performance of metal-oxide-semiconductor field-effect-transistors (MOSFETs). [14][15][16][17][18][19][20][21][22] A few review articles have covered aspects such as uniaxial and biaxial strain on carrier mobility in MOSFETs, [23][24][25][26] with a theoretical analysis of the physics of strained MOSFETs for different wafer surface orientations, channel directions, gate electric fields, and materials. 23,24,26 These studies have positive implications for similar investigations in bendable or flexible electronics.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Modulation doping has been widely used in III-V compound heterojunction superlattices to eliminate the influence of ionized impurity scattering. [14][15][16] In the heterojunction device, the ionized dopants and electrons are confined to two different adjacent layers. As a result, both the mobility and carrier concentration are well maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding advancement in the quality of 2-D electron systems in Si has been lagging behind as far as their quality at cryogenic temperatures is concerned, in spite of the very mature Si MOSFET technology. In 1984, People et al first observed the two-dimensional hole gas (2DHG) in modulation-doped Si 0.8 Ge 0.2 films grown on Si (001) substrates [4]. In the following year, Abstreiter et al studied strained silicon grown on partially relaxed Si 1 − x Ge x substrate with type-II band alignment and observed the presence of two-dimensional electron gas in Si [5].…”
Section: History Of 2deg Research In Si/sige Heterostructuresmentioning
confidence: 97%